Differences in Student Learning Outcomes Between Multiplication Board and Abacus Media in Grade II of Elementary School - Mifrokhatul 'Izza, Kamalia; Suryandari, Suryandari; Albarra Shidiq, Galih; Dwi Ariyani, Yusinta (DAS Institute, 2025)
Multiplication, as one of the materials found in elementary schools, is often taught using the rote method, so that the concept of multiplication is not ingrained in students. Therefore, it is necessary to use learning media in teaching multiplication so that students better understand the concept of multiplication. The learning media used in this research are the multiplication board and abacus. The aims of this research are 1) to find out differences in student learning outcomes, 2) to find out differences in students' psychomotor skills, 3) to find out better learning outcomes, and 4) to find out better psychomotor skills. This research is experimental research with the research subjects being second grade elementary school students. This research uses test instruments to determine student learning outcomes as well as observation sheets to determine students' psychomotor skills. This research was carried out in the odd semester of the 2024/2025 academic year at the Kasihan State Elementary School. The results of this research are 1) there is no difference in learning outcomes, 2) there is no difference in psychomotor skills, 3) the learning outcomes of students using the multiplication board are better, 4) the psychomotor skills of students using the abacus are better. Even though there was no difference in learning outcomes and psychomotor skills, there was an increase in learning outcomes between the pretest and posttest and an increase in psychomotor skills between the first meeting and the second meeting.